Foliar endophyte diversity in Eastern Asian-Eastern North American disjunct tree species – influences of host identity, environment, phylogeny, and geographic isolation - Zhou, Wenbin; Shi, Wei; Soltis, Pamela S.; Soltis, Douglas E.; Xiang, Qiu-Yun (Jenny) (Frontiers in Plant Science, 2023)
The well-known eastern Asia (EA) and eastern North America (ENA) floristic disjunction provides a unique system for biogeographic and evolutionary studies. Despite considerable interest in the disjunction, few studies have investigated the patterns and their underlying drivers of allopatric divergence in sister species or lineages isolated in the two areas. Endophyte diversity and assembly in disjunct sister taxa, as an ecological trait, may have played an important role in the processes of allopatric evolution, but no studies have examined endophytes in these lineages. Here, we compared foliar endophytes (including fungi FEF and bacteria FEB) in 17 EA-ENA disjunct species or clade pairs from genera representing conifers and 10 orders of five major groups of angiosperms and 23 species of Cornus from EA and NA. We gained insights into the relative roles of historical geographic isolation, host identity, phylogeny from samples at the same site, and environment from samples at different sites in shaping endophytic diversity patterns. We found that beta diversity of endophytes varied greatly among plant individuals within species and between species among genera at the same sampling site, and among three sampling sites, but little variation between region-of-origin of all plant species (EA vs ENA) and between EA-ENA disjunct counterparts within genera. Various numbers of indicator fungal species different in abundance were identified for each plant genus and Cornus species. An overall significant correlation between endophyte community dissimilarity and phylogenetic distance of plants was detected among the disjunct genera but not among species of Cornus. However, significant correlations between beta diversities at different taxonomic scales of endophytes and phylogenetic distances of Cornus species were observed. Our results suggest important roles of host identity and environment (sampling sites), and a likely minor role of phylogenetic divergence and historical biogeographic isolation in shaping the pattern of foliar endophyte diversity and assembly in the EA-ENA disjunct genera and Cornus. The results lead to a hypothesis that the sister taxa in EA and ENA likely differ in FEF and FEB when growing in native habitats due to differences in local environments, which is may potentially drives allopatric divergence of species functional features.